(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Cesium in-cooperated in Mobile Composite Matter Number 41 (CsMCM-41) was synthesized via hydrothermal synthesis. The material used involve Ludox AS-40 as silica (SiO2) source, aluminum isoproxide as alumina (Al2O3) source, Cesium hydroxide (CeOH) as mineralizer. CsMCM-41 was characterized using X-ray diffraction (XRD), N2 adsorption-desorption isotherms and X-ray fluorescence (XRF) spectroscopy. The sample shows a high surface area (685 m2 g-1), large pore volume (0.99 m2g-1), and 20.7 Ao as its pore size. The basicity of the sample was determine using back titration to obtained 101.57 mmol g-1. CsMCM-41 was used as heterogeneous solid base catalyst which is more environmentally friendly to synthesize jasminaldehyde via an aldol condensation reaction between benzaldehyde and heptanal at different temperature and reaction time. This replace the homogeneous base (NaOH, KOH) catalyst that produce corrosive bases as a waste. Four different heating methods were studied. Microwave, non-microwave instant heating, oven and refluxing method. The microwave heating method gave higher conversion (78.2%) and higher selectivity (70.2%) to jasminaldehyde at 180oC in 45 min. as a result of minimized heat loss displayed by the apparatus. Oven synthesis method gave lower conversion (29.4%) and lower selectivity (53.1%), at 180oC at a longer reaction time (24 hours), which resulted due to heat loss to the surrounding. Microwave irradiation was found to be the best heating method for jasminaldehyde synthesis. The catalyst (Cs-MCM-41) is environmentally friendly and can be recycled number of times (up to 5 times), without catalyst deactivation at the same time no waste generated.